Provider reported value and use of virtual resources in extended primary care prior to and during COVID-19 - Jolie N. Haun; Vanessa Panaite; Bridget A. Cotner; Christine Melillo; Hari H. Venkatachalam; Christopher A. Fowler; Brian Zilka; William Messina (BMC, 2022)
Abstract Background A proactive approach to delivering care using virtual resources, while reducing in-person contact, is needed during the COVID-19 pandemic. Objective In the current study we describe pre- to post- COVID-19 pandemic onset related changes in electronic delivery of primary care. Methods A longitudinal, pre-post within-subjects design was used. Patient-aligned care team providers from one VA medical center, a primary care annex, and four affiliated community-based outpatient clinics completed both a baseline and follow up survey (N = 62) or the follow-up survey only (N = 85). The follow-up survey contained questions about COVID-19. Results The majority of providers (88%) reported they would continue virtual care once pandemic restrictions were lifted. Most (83%) felt prepared to transition to virtual care when pandemic restrictions began. Use of My HealtheVet, Telehealth, and mobile apps showed a significant increase (22.7%; 31.1%; 48.5%). Barriers to virtual care included (1) internet connectivity; (2) patients' lack of technology comfort and skills; and (3) technical issues. Main supports to provide virtual care to patients were (1) peers/ colleagues; (2) technology support through help desk; (3) equipment such as laptops and dual screens; (4) being able to use doximety and virtual care manager, and (5) training. Conclusions Overall, provider-use and perceptions related to using virtual care improved over time. Providers adapted quickly to providing virtual care during COVID-19 and planned to provide virtual care long-term.